Pengaruh Leverage, Likuiditas dan Kinerja Perusahaan terhadap Risiko Sistematis Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI) - Masdupi, Erni; Noberlin, Sylvia (Jurusan Manajemen Fakultas Ekonomi Universitas Negeri Padang, 2015)
The purpose of this research is to analyze the influence of leverage, liquidity and company performance on systematic risk of manufacturing companies. The population of this research is all manufacturing companies which listed in Indonesian Stock Exchange in the period of 2008-2012. Sample was chosen by purposive sampling method, so the sample of this research is 60 companiy-year observations Analysis method is multiple regression. The result showed that leverage (debt ratio) and ikuidity (current ratio) had negative and not significant effect on systematic risk (beta) while company performance had negative and significant influence on systematic risk (beta).